ANALISIS KESALAHAN DALAM MENYELESAIKAN SOAL CERITA PADA MATERI HIMPUNAN BERDASARKAN TAHAPAN NEWMAN - Riska Nurdiawan; Luvy Sylviana Zanthy (Departement of Mathematics Education, 2019)
This study aims to answer the questions that have been formulated, namely: (1) the types of mistakes made by the subject in solving the set questions; (2) the cause of an error made by the subject in working on set questions. Classifying the types of errors according to Newman, namely reading errors, misunderstanding, transformation errors, process skill errors and errors writing the final answer. This study uses descriptive qualitative. The subject of this study was seventh grade students of Al-Mubarokah MTs. Subject collection using purposive sampling technique. Data was taken using the description test method. In this study the questions used were 5 questions about set stories. The results showed that the three subjects made mistakes in understanding, errors in transforming and errors in process skills. The cause of this error is because the subject does not know what is actually being asked about the problem, misunderstands the information in the question so that it cannot complete the next process, does not understand how to change into a mathematical model and is not skilled in calculating.